THE INFLUENCE OF THE LENGTH OF COAL SHIP UNLOADING TIME ON THE NUMBER OF VISITS OF VESSELS AGENT BY PT. ADHIKA SAMUDERA JAYA NORTH MOROWALI BRANCH - Trisna, Yoga Yulinda; Rahmawati, Maulidiah; Ratnaningsih, Dyah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pelayaran Malahayati, 2025)
Sea transportation is very necessary to support trade activities which are expected to develop both in quality and quantity. Along with the increase in trade in goods via sea transport routes. The demand for goods via sea transportation cannot be separated from the loading and unloading activities of goods from one port to another. Especially in the process of loading and unloading activities, obstacles often arise, causing delays in the ship's berthing time that are longer than the specified time. The aim of this research is to find out how long the unloading time for coal ships affects the number of ship visits. This research uses quantitative research methods. Data analysis is used to prove the influence of variable X on variable Y, such as correlation coefficient analysis, coefficient of determination analysis, simple linear regression analysis, and hypothesis testing. The results of this research obtained a relationship or correlation (r) of 0.986. From this value, the coefficient of determination (R square) is 0.971, so it can be interpreted that the effect of the length of unloading time (X) on the number of ship visits (Y) is 97.1%, with the result of the hypothesis test value T calculated 18.460 > T table 1.812 . It can be concluded that the variable influencing the length of unloading time on the number of ship visits has a strong and significant influence.